Hubungan Tipe Kepribadian Dengan Penyesuaian Diri Mahasiswa Perantau di Universitas Tarumanagara Jakarta - Untung Subroto; Linda Wati; Monty P. Satiadarma (Provitae: Jurnal Psikologi Pendidikan, 2018)
This study aims to look at the relationship between personality types and self-adjustment of migrant students in Universitas Tarumanagara. Personality defined as a pattern of unique characteristics and relatively permanent traits, which are individuality and consistency in an individual’s behavior. Self-adjustment can be said as the changes which made to the environment as an effort to fit with the individual. The design of this study is quantitative, non-experimental to see whether there is a personality relationship to the adjustment of migrant psychology students at Tarumanagara University. The number of research subjects was 62 students consisting of 12 male and 50 female psychology students at Tarumanagara University who were all overseas students from various regions in Indonesia. These participants filled in the Big 5 Personality questionnaire. This reseach aimed at finding the personality tendency that supports the migrant students to get adjusted easier in the new living environment. Findings indicate that both ‘agreeableness’ and ‘conscientiousness’ aspects of the Big 5 Personality have greater contribution on individual’s self-adjustment than the other three aspects. In other words, individuals who are more ‘agreeable’ and ‘conscientious’, tend to have better ability to adjust socially and emotionally. Personality aspects play a role in the situation which shows the success of students to adjust to the environment.